Reformulação para um problema integrado de dimensionamento e sequenciamento de lotes - Bernardes, Eduardo Delcides [UNESP]; Araujo, Silvio Alexandre de [UNESP]; Rangel, Socorro [UNESP] (FapUNIFESP (SciELO), 2010)
In this paper, some new constraints and an extended formulation are presented for a Lot Sizing and Scheduling Model proposed in the literature. In the production process considered a key material is prepared and is transformed into different final items. The sequencing decisions are related to the order in which the materials are processed and the lot sizing decisions are related to the final items production. The mathematical formulation considers sequence-dependent setup costs and times. Results of the computational tests executed using the software Cplex 10.0 showed that the performance of the branch-and-cut method can be improved by the proposed a priori reformulation.
Keywords: A priori reformulation; Extended formulation; Lot sizing and scheduling; Mixed-integer programming; Production planning